Hot Quadrate Sign Under Focus of F18-FDG PET-CT: An Incidental Finding - Ayesha Zubair; Aamna Hassan (Journal of the Pakistan Medical Association, 2024)
“Hot quadrate lobe sign” refers to visualization of caudate lobe of liver due to excess accumulation of radiotracer secondary to superior vena cava obstruction. Collateral channels are formed between thoracic and mediastinal vessels; internal mammary through the paraumbilical vessels which drain blood to the left portal vein and into the caudate lobe of liver. It was first described on Tc99-m sulfur colloid scan. We present a case with superior vena cava obstruction presenting as hot quadrate lobe sign on F18-FDG PET-CT. Keywords: F18-FDG PET-CT, caudate lobe, superior vena obstruction, collateral vessels.